Externalities in Recruiting - Matthias Kräkel; Frauke Lammers; Nora Szech (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
According to the previous literature on hiring, ?rms face a trade-off when deciding on external recruiting: From an incentive perspective, external recruiting is harmful since admission of external candidates reduces internal workers' career incentives. However, if external workers have high abilities hiring from outside is bene?cial to improve job assignment. In our model, external workers do not have superior abilities. We show that external hiring can be pro?table from a pure incentive perspective. By opening its career system, a ?rm decreases the incentives of its low-ability workers. The incentives of high-ability workers can increase from a homogenization of the pool of applicants. Whenever this effect dominates, a ?rm prefers to admit external applicants. If vacancies arise simultaneously, ?rms face a coordination problem when setting wages. If ?rms serve the same product market, weaker ?rms use external recruiting and their wage policy to offset their competitive disadvantage.
Keywords: C72; J2; J3; 330; Contest; externalities; recruiting; wage policy; Personalbeschaffung; Interner Arbeitsmarkt; Externer Effekt; Leistungsanreiz; Lohnpolitik; Wettbewerb; Theorie